1989
DOI: 10.1111/j.1469-7998.1989.tb02601.x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental examination of the colour component in visually mediated sexual arousal of the male chacma baboon (Papio ursinus)

Abstract: Male chacma baboon (Papio ursinus) sexual arousal response as gauged by the coagulated seminal emissions resultant from masturbatory activity was experimentally assessed. Males were initially exposed to an ovariectomized female prior to and during daily oestradiol benzoate treatment. Males were then re‐exposed to the same female prior to and during the wearing of a thermoplastic model of a swollen female perineum. A total of eight different colours were sequentially applied to the model. It was only the red mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 23 publications
0
35
1
Order By: Relevance
“…Bielert & Van der Walt (1982), for example, found that the masturbatory behaviour and serum testosterone concentration of male chacma baboons, Papio ursinus, exposed to visual contact with females were linked to sexual swelling size, being greatest at the time when the swelling was at its peak. Further work, in which arti¢cial swellings were attached to ovariectomized females, produced evidence that this relationship is due to the visual stimulus of the swelling itself and not to other potentially confounding variables, such as vocal or olfactory signals (Bielert et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Bielert & Van der Walt (1982), for example, found that the masturbatory behaviour and serum testosterone concentration of male chacma baboons, Papio ursinus, exposed to visual contact with females were linked to sexual swelling size, being greatest at the time when the swelling was at its peak. Further work, in which arti¢cial swellings were attached to ovariectomized females, produced evidence that this relationship is due to the visual stimulus of the swelling itself and not to other potentially confounding variables, such as vocal or olfactory signals (Bielert et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Anogenital swellings are highly developed in several primate species [Short, 1977[Short, , 1979[Short, , 1981, where they are believed to be attractive to males [Bielert et al, 1989]. Clutton-Brock and Harvey [1976] originally noted that species with exaggerated sexual skin swellings live in multi-male social systems.…”
Section: Introductionmentioning
confidence: 99%
“…Selectivity, of course, implies some cost of mating for males: time spent developing a consortship, increased risk of attracting ag gression from other males or contracting ve nereal disease, and decreased fertility in sub sequent matings due to sperm depletion are all possible costs of mating which will tend to be higher in species with multimale social sys tems. Consistent with this hypothesis, the sex ual attractiveness of a female seems to in crease with the size of the sexual swelling, though other factors are important as well [4,[40][41][42], Thus there are two seemingly reasonable theories for the conspicuousness of some sex ual signals, both with some anecdotal support, but neither is as yet compelling. August 16-21, 1992, Strasbourg, France…”
Section: Conspicuous Sexual Signalsmentioning
confidence: 69%